Pengaruh Pelatihan Akuntansi, Pendidikan Pemilik dan Umur Usaha terhadap Penggunaan Informasi Akuntansi pada UMKM - Jessica Tan; Dian Efriyenty (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Business development entails making numerous decisions. Every business decision is of course based on careful considerations, one of which is accounting information. By using appropriate accounting information, it will help business actors make it easier to make business strategies and decisions so as to support development and sustainable business. This research aims to ascertain the impact of accounting training, owner education, and business age on the use of accounting information. This research employs a quantitative methodology. The sample population for this study consisted of 81,575 MSMEs who were officially registered at the Batam City Cooperatives and Micro, Small and Medium Enterprises Department. The study's sample consisted of 100 MSMEs, determined using the Slovin formulation and drawn using a simple random sampling procedure.The t-test revealed that accounting training, owner education, and firm age all had a statistically significant impact on the use of accounting information. Meanwhile, the f test revealed that Accounting Training, Owner Education, and Business Age all had a substantial impact on the use of accounting information.